2021
DOI: 10.3390/ma14195779
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Dielectric Properties of Ni-Doped In2S3 Powders for Optical Windows in Thin Film Solar Cells

Abstract: This paper reports the effect of Nickel (Ni) on indium sulfide (In2S3) powder. This work presents a systematic study of the physical and dielectric properties of In2-xS3Nix powders with 0, 2, 4, and 6 at.% of nickel. Doped and undoped samples were investigated by X-ray powder diffraction (XRD), energy dispersive X-ray spectroscopy, thermal gravimetric analysis, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), and impedance spectroscopy. XRD patterns reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Analyzing the atomic layers of the FTIR spectrum at 1100 𝑐𝑚 −1 shows fewer peaks, and this is in agreement with the poor selectivity of CH4 [33]. It has been found that the extended bonds at (800 𝑐𝑚 −1 to 1500 𝑐𝑚 −1 ) correspond to C = O, O-H and also C-H, O-H [34].…”
Section: Ftir Spectroscopysupporting
confidence: 69%
“…Analyzing the atomic layers of the FTIR spectrum at 1100 𝑐𝑚 −1 shows fewer peaks, and this is in agreement with the poor selectivity of CH4 [33]. It has been found that the extended bonds at (800 𝑐𝑚 −1 to 1500 𝑐𝑚 −1 ) correspond to C = O, O-H and also C-H, O-H [34].…”
Section: Ftir Spectroscopysupporting
confidence: 69%
“…Different configurations of the vacancy screws allow it to crystallise in one of many different space groups, including P6 1 , P6 5 , P6 1 22, or P6 5 22. 39,40 There are plenty of forms of Indium sulfide and Indium selenide available, such as self-assembled porous 3D flowerlike b-In 2 S 3 , 41 nanoparticles of In 2 S 3 , 42 b-In 2 S 3 nanoplates, 43 1D b-In 2 S 3 /In 2 O 3 micro-tubes, 44 In 2 S 3 thin film, 45 In 2 S 3 /BiOI composites, 46 Ni-doped In 2 S 3 powders, 47 nanosheets of In 2 S 3 / S-C 3 N 4 -dots, 48 In 2 S 3 quantum dots, 49,50 In 2 S 3 single crystal, 51,52 g-In 2 S 3 and b-In 2 S 3 colloidal nanoplatelets, 26 hierarchical Bi 2 S 3 / In 2 S 3 core/shell microspheres, 53 In 2 Se 3 nanowires, 54 monolayer b-In 2 Se 3 nanosheets, 55 etc.…”
Section: Introductionmentioning
confidence: 99%